Raising the bar in respiratory care by EUFOREA: report of the European Union Parliament Symposium, April 2024 - Hellings, P. W.; Conti, D. M.; Bertels, X.; Backer, V.; Brusselle, G.; De Corso, E.; Fokkens, W. J.; Fox, A. T.; Gevaert, P.; Lau, S.; Liva, G.; Palkonen, S.; et al. (Frontiers in Allergy, 2025)
In April 2024, the European Summit “Raising the bar in respiratory care” was organized by the European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) in the European Parliament and hosted by Members of the European Parliament Dorien Rookmaker and Mislav Kolakušić. The aim of the Summit was to respond to the need of European patients suffering from chronic respiratory diseases (CRDs) by joining forces with European and global organisations in the management of the epidemics of CRD, recognising the weaknesses of current care models and focussing on collaboration to improve care and prevention. Participants belonging to International and National Societies and Committees from the European Rhinologic Society (ERS), International Rhinologic Society (IRS), Belgian Respiratory Society (BeRS), Global Initiative for Asthma (GINA), Global Initiative for Chronic Obstructive Lung Disease (GOLD), Global Alliance against Chronic Respiratory Diseases (GARD), and from the European Federation of Allergy and Airways Diseases Patients Associations (EFA) and the EUFOREA's Patient Advisory Board (PAB) described their vision and action plan to work in partnership to raise the bar in respiratory care. This report summarizes the contributions of the representatives of different European stakeholders in the field of CRDs.